Voltage unbalance compensation in an islanded microgrid system with unbalanced transmission lines - Su, Yi (2016)
Recently, the new concept of microgrid hierarchical control is published. Smart grid is described as a power system which make fully use of state-of-the-art sensing and monitoring system as well as information and communication technology.